2017
DOI: 10.1016/j.anai.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of current pediatric epinephrine autoinjector needle length for use in infants and toddlers

Abstract: Our data suggest that the optimal EAI needle length for infants and toddlers weighing 7.5 to 15 kg should be shorter than the needle length in currently available pediatric EAIs to avoid accidental intraosseous injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…There are also some concerns about the needle length of the AAIs. Recent studies using ultrasound have shown that certain AAIs may be associated with a risk of adrenaline bone injection . The optimal needle length of AAI to ensure optimal adrenaline diffusion requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are also some concerns about the needle length of the AAIs. Recent studies using ultrasound have shown that certain AAIs may be associated with a risk of adrenaline bone injection . The optimal needle length of AAI to ensure optimal adrenaline diffusion requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The declared variation in pressure that is accepted by companies for release of new batches, applied to EAIs has been presented elsewhere [9]. There are instruments that can apply a specified pressure to the ultrasound probe and such instruments should be used in all future trials and in the instruction to prescribing health care personnel [10,11]. Furthermore, we propose the variation in needle length and the influence of thick clothes should be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some children may need shorter needles and may in fact be at risk of having the needle penetrate bone. 42 The US Food and Drug Administration recently approved a shorter needle for an epinephrine autoinjector (Auvi-Q) to be used in children weighing 7.5 kg to 15 kg.…”
Section: Obese Patients May Need a Longer Needlementioning
confidence: 99%